IgE autoantibodies in serum and skin of non‐bullous and bullous pemphigoid patients. (17th November 2020) - Lamberts, A.; Kotnik, N.; Diercks, G.F.H.; Meijer, J.M.; Di Zenzo, G.; Pas, H.H.; Jonkman, M.F.; Gibbs, B.F.; Raap, U.; Horváth, B.
Abstract: Background: Non‐bullous pemphigoid (NBP) is a pemphigoid variant which frequently resembles other pruritic skin diseases. In contrast with bullous pemphigoid (BP), blisters are absent. In BP, previous studies showed that IgE autoantibodies may be involved in its pathogenesis. IgE‐activated mast cells, basophils and eosinophils may participate in BP by inducing pruritus and possibly blister formation, although the differential role of IgE in NBP compared with BP has not yet been described. Objective: To assess IgE in serum and skin of NBP and BP patients. Methods: We examined total IgE and pemphigoid‐specific IgE in the serum of 68 NBP and 50 BP patients by enzyme‐linked immunosorbent assay (ELISA). Sera of 25 pemphigus patients and 25 elderly patients with pruritus were included as controls. Skin biopsies of 14 NBP and 14 BP patients with the highest IgE titres to NC16A were stained for IgE by immunofluorescence techniques. Results: Total IgE was elevated in 63% of NBP and 60% of BP patients, and in 20% of pemphigus controls, as well as 60% of elderly controls. IgE ELISAs were more frequently positive in BP than in NBP (NC16A 18% vs. 9%, P = 0.139; BP230 34% vs. 22%, P = 0.149). IgE ELISAs for NC16A and BP230 were positive in 8% and 20% of elderly controls, respectively, while all pemphigus controls were negative. Two of 28 biopsies (7%; one NBP, one BP) showed linear IgE along the basement membrane zone, while in most biopsies (71% NBP; 86% BP) IgE was bound to dermal cells. Conclusion: Since IgE was present in the serum and skin of both NBP and BP patients, this supports IgE‐dependent mechanisms common to both diseases, such as pruritus. However, it remains to be elucidated whether IgE contributes to blister formation in BP. Abstract : Linked Commentary : I. Kortekaas Krohn. J Eur Acad Dermatol Venereol 2021; 35: 781–782. https://doi.org/10.1111/jdv.17164 .